Kinetic optimization of angkak – red ginger extraction and its impact on antioxidant activity - Missy, Felesia; Fahrurroji, Andhi; Nugraha, Fajar; Anastasia, Desy Siska (Jurnal Teknosains, 2024)
A mixture of angkak and red ginger is a Chinese herbal concoction with potential as an antioxidant. This herbal combination can be extracted using the kinetic hot maceration method by optimizing the stirring speed to be more efficient. Previous studies have shown that using 400, 600, and 800 rpm stirring speeds provides the best IC50 and yield. Based on these problems, this research aims to determine the effect of increasing stirring speed on IC50 and % yield in the extraction of angkak and red ginger, as well as prove the benefits of this herbal combination through the IC50 value. The method used is extracting a mixture of angkak and red ginger at kinetic variations of 400, 600, and 800 rpm using a magnetic hotplate stirrer at a temperature of 60ºC for 2 hours; determination of % yield; determining the chromatogram profile using TLC; determination of antioxidant activity using DPPH; as well as data analysis of percentage yield and IC50 using SPSS. Analysis using SPSS shows that the stirring speed significantly affects the % yield, where increasing the moving speed above 400 rpm results in a decrease in the % yield. However, the moving speed does not affect the IC50. The TLC chromatogram profile shows the presence of 6-gingerol compounds in angkak and red and yellow pigment compounds in red ginger, which have potential as antioxidants. The optimization results in this study obtained optimal % yield and IC50 at 400 rpm with average values, respectively, namely 15.933 ± 3.4771% and 103.76 ± 10.032 ppm, and the combination of angkak and red ginger ingredients can work synergistically to increase yield and antioxidant.